PROSES PENYUSUNAN INSTRUMEN SUPERVISI DAN ANALISIS KUALITAS PELAPORAN KINERJA PADA MADRASAH - Nabil Achmad Aufani; Nurjamilatul Muhairira; Diska Firzan Nadia Fatiq; Indah Aminatuz Zuhriyah; Baharuddin Baharuddin (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2025)
Supervision is a form of supervision or assessment carried out by school principals to improve the quality or quality of education of an institution. Therefore, an institution must really pay attention to supervision activities. To create good supervision activities, it is necessary to have supporting instruments, as in MI Islamiyah Malang has a strategy and process on how to prepare supervision instruments and analyze the quality of education reporting. The method used in this study is a qualitative method, while the data collection techniques used are observation, interviewing and documentation with the Miles and Huberman model data analysis techniques including data collection, data reduction, data reduction and drawing conclusions with the data validity technique of source triangulation. The results of the research show that the strategy used by the principal of MI Islamiyah Malang in supervision is by utilizing technology, adapting to members' needs and analyzing age levels. And for the process of preparing supervision instruments, namely by carrying out planning stages or pre-observation, observation and follow-up processes. Then finally, the reporting analysis carried out by MI Islamiyah Malang is collecting, verifying and classifying, summarizing, calculating, storing and retrieving, reproducing and finally communicating.